Who creates luxury? Unveiling the essence of luxury creation through three perspectives : a scoping review - Gummerus, Johanna; von Koskull, Catharina; Kauppinen-Räisänen, Hannele; Medberg, Gustav (Emerald, 2023)
Purpose Past research on luxury is fragmented resulting in challenges to define what the construct of luxury means. Based on a need for conceptual clarity, this study aims to map how research conceptualises luxury and its creation. Design/methodology/approach This study presents a scoping review of luxury articles published in peer-reviewed journals. Of the initial 270 articles discovered by using the database of Scopus, and after control searching in Web of Science and reference scanning, 54 high-quality studies published before the end of 2020 were found to meet the inclusion criteria and comprised the final analytical corpus. Findings The findings demonstrate that research approaches luxury and its creation from three different perspectives: the provider-, consumer- and co-creation perspectives. In addition, the findings pinpoint how the perspectives differ from each other due to fundamental and distinguishing features and reveal particularities that underlie the perspectives. Research limitations/implications The suggested framework offers implications to researchers who are interested in evaluating and developing luxury studies. Based on the identified luxury perspectives, the study identifies future research avenues. Originality/value The study contributes to the luxury research stream by advancing an understanding of an existing pluralistic perspective and by adding conceptual clarity to luxury literature. It also contributes to marketing and branding research by showing how the luxury literature connects to the evolution of value creation research in marketing literature.
Keywords: Co-creation; Conceptual development; Luxury perspectives; Scoping review; luxury; fi=Markkinointi|en=Marketing|